Simpson’s Instructional Model (SIM) for the Development of Walking Tractor Driving Skills for Crop Production Students - Dowroong Watcharinrat (International Journal of Advanced Science and Technology, 2020)
The objectives of this study were: 1) to compare walking tractor driving skills of the student after a study by Simpson’s Instructional Model (SIM) between group 1 and group 2, and 2) to compare walking tractor driving skills of the student after a study by SIM between males and females. The research worked with fifty-one students divided into two groups. The first group, Group 1, was taught by technical staff, and the second group, Group 2, was taught by a lecturer. This research initially evaluated students’ motor vehicle driving skills before the SIM was applied. After practical teaching for a month, students were evaluated their skills again by demonstrated driving the walking tractor. Mean, standard deviation, frequency, percentage, and t-test used in this research were statistics. The result showed in mean that after a month, the students in group1 had similar skills in driving the walking tractor to the group 2 students and the skills of male students had similar to the female students. There was no significant difference in the statistical t-test between group 1 and group 2 at level 0.05, also t-test between male and female students at 0.05.Keywords: walking tractor, agricultural machinery, Simpson’s Model